THE INFLUENCE OF CORE COMPETENCE, MARKETING MIX STRATEGY AND MARKETING RELATIONSHIP STRATEGY TOWARD COMPETITIVE ADVANTAGE AND ITS IMPLICATION ON MARKETING PERFORMANCE (Survei Of Buku 2 Banks In West Java Province And DKI Jakarta) - Tatang Supriyadi; Sucherly; Undang juju (Jurnal Ekonomi, 2022)
This research tries to explain and analyze the influence of core competence, marketing mix strategy and marketing relationship strategy toward competitive advantage and its implication on marketing performance. This research uses a descriptive-verificative method with a causal approach that aims to explain the influence between variables. The data used is primary data at BUKU 2 banks in West Java Province and DKI Jakarta which were collected through a questionnaire of 381 respondents. Descriptive analysis was performed by tabulating the data for the determination of the average value category, for verification analysis using Structural Equation Modelling (SEM) and LISREL data processing. The descriptive test shows that Core Competence including in the Fairly Competent category, Marketing Mix Strategy including in the Less Good category, Marketing Relationship Strategy included in the category Fairly Good, Competitive Advantage in Fairly Excellent category, and Marketing Performance with Fairly High category. The verification test shows that there is a significant effect of Core Competence, Marketing Mix Strategy, Marketing Relationship Strategy on Competitive Advantage. Thus, simultaneously the variables of Core Competence, Marketing Mix Strategy and Marketing Relationship Strategy provide a significant contribution to the formation of Competitive Advantage. Likewise, Competitive Advantage has a positive effect and significant on Marketing Performance at BUKU 2 banks in West Java Province and DKI Jakarta.